Marriage, fertility and the family in Ireland ? a statistical perspective - Punch, Aidan (Statistical and Social Inquiry Society of Ireland, 2007)
The paper looks at the changes which have been occurring in trends relating to marriage, fertility, and the family in Ireland. Cohabitation is increasing with one in four couples without children now falling into this category. On the other hand, marriage is occurring at older ages although there is evidence of a stabilisation of the decline in the probability of females marrying for the first time. The increase in the average age at which females are having their first child is consistent with later marriages while the narrowing of the differential between the average ages for different birth orders suggests that the spacing of children is now concentrated over a shorter period of time than heretofore. While the predominant family type still consists of husbands and wives and their children, the growth in the number of couples without children clearly reflects a lifestyle choice on the part of certain couples. The increase in the number of usual residents of this country who were born abroad has begun to impact on the make up of the family in Ireland. One of the fastest growing categories has been children born in this country to parents, both of whom were born outside Ireland and the UK. It is clear from the information presented in the paper that Ireland is experiencing major demographic change at present.
Presidential address read before the Society, 31 May 2007
Keywords: Marriage; Fertility; Family; 314.15